Tm and Tm-Tb-doped germanate glasses for S-band amplifiers - Librantz, A. F. H.; Gomes, L.; Pairier, G.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V., 2008)
The mechanism involved in the Tm(3+)((3)F(4)) -> Tb(3+)((7)F(0,1,2)) energy transfer as a function of the Tb concentration was investigated in Tm:Tb-doped germanate (GLKZ) glass. The experimental transfer rate was determined from the best fit of the (3)F(4) luminescence decay due to the Tm -> Tb energy transfer using the Burshtein model. The result showed that the 1700 nm emission from (3)F(4) can be completely quenched by 0.8 mol% of Tb(3+). As a consequence, the (7)F(3) state of Tb(3+) interacts with the (3)H(4) upper excited state of TM(3+) slighting decreasing its population. The effective amplification coefficient beta(cm(-1)) that depends on the population density difference Delta n = n((3)H(4))-n((3)F(4)) involved in the optical transition of Tm(3+) (S-band) was calculated by solving the rate equations of the system for continuous pumping with laser at 792 nm, using the Runge-Kutta numerical method including terms of fourth order. The population density inversion An as a function of Tb(3+) concentration was calculated by computational simulation for three pumping intensities, 0.2, 2.2 and 4.4 kWcm(-2). These calculations were performed using the experimental Tm -> Tb transfer rates and the optical constants of the Tm (0.1 mol%) system. It was demonstrated that 0.2 mol% of Tb(3+) propitiates best population density inversion of Tin(3+) maximizing the amplification coefficient of Tm-doped (0.1 mol%) GLKZ glass when operating as laser intensity amplification at 1.47 mu m. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: germanate glasses; Rare earth ions; Optical absorption and laser induced luminescence; Non-radiative energy transfer; Population inversion; CW laser pumping and rate equations; Tm based optical amplifier properties for 1470 nm